Andesites of the 2009 eruption of Redoubt Volcano, Alaska - Coombs, Michelle L.; Sisson, Thomas W.; Bleick, Heather A.; Henton, Sarah M.; Nye, Chris J.; Payne, Allison L.; Cameron, Cheryl E.; Larsen, Jessica F.; Wallace, Kristi L.; Bull, Katharine F. (Journal of volcanology and geothermal research, 2013)
Crystal-rich andesites that erupted from Redoubt Volcano in 2009 range from 57.5 to 62.5wt.% SiO2 and have phenocryst and phenocryst-melt relations consistent with staging in the upper crust. Early explosive products are low-silica andesites (LSA, <58wt.% SiO2) that ascended from deeper crustal levels during or before the 6months of precursory activity, but a broad subsequent succession to more evolved and cooler products, and predominantly effusive dome growth, are interpreted to result from progressive mobilization and mixing with differentiated magmas tapped from pre-2009 Redoubt intrusions at ~3–6km depth. Initial explosions on March 23–28 ejected predominantly LSA with a uniform phenocryst assemblage of high-Al amphibole, ~An70 plagioclase, ortho- and clinopyroxene, FeTi oxides (890 to 960°C), and traces of magmatic sulfide. Melt in the dominant microlite-poor LSA was compositionally uniform dacite (67–68wt.% SiO2) but ranged to rhyolite with greater microlite growth. Minor amounts of intermediate- to high-silica andesite (ISA, HSA; 59–62.5wt.% SiO2) also erupted during the early explosions and most carried rhyolitic melt (72–74wt.% SiO2). A lava dome grew following the initial tephra-producing events but was destroyed by an explosion on April 4. Ejecta from the April 4 explosion consists entirely of ISA and HSA, as does a subsequent lava dome that grew April 4–July 1; LSA was absent. Andesites from the April 4 event and from the final dome had pre-eruptive temperatures of 725–840°C (FeTi oxides) and highly evolved matrix liquids (77–80wt.% SiO2), including in rare microlite-free pyroclasts. ISA has mixed populations of phenocrysts suggesting it is a hybrid between HSA and LSA. The last lavas from the 2009 eruption, effused May 1–July 1, are distinctly depleted in P2O5, consistent with low temperatures and high degrees of crystallization including apatite. Plagioclase–melt hygrometry and comparison to phase equilibrium experiments are consistent with pre-eruptive storage of all three magma types at 100–160MPa (4–6km depth), if they were close to H2O-saturation, coincident with the locus of shallow syn-eruptive seismicity. Deeper storage would be indicated if the magmas were CO2-rich. Relatively coarse-grained clinopyroxene-rich reaction rims on many LSA amphibole phenocrysts may result from slow ascent to, or storage at, depths shallow enough for the onset of appreciable H2O exsolution, consistent with pre-eruptive staging in the uppermost crust. We interpret that the 2009 LSA ascended from depth during the 8 or more months prior to the first eruption, but that the magma stalled and accumulated in the upper crust where its phenocryst rim and melt compositions were established. Ascent of LSA through stagnant mushy intrusions residual from earlier Redoubt activity mobilized differentiated magma pockets and interstitial liquids represented by HSA, and as LSA–HSA hybrids represented by ISA, that fed the subsequently erupted lava domes. ► 2009 Redoubt eruption produced andesites with 57–62.5 wt% SiO2. ► Early explosions dominated by low-silica andesite, later effusive activity by high- and intermediate-silica andesites. ► Magmas staged at 4–6km depth before eruption, but low-silica andesite ascended from lower crust in the ~8 months prior. ► Ascent of low-silica andesite through mushy intrusions mobilized differentiated magma pockets (high-silica andesites).